Compositional analysis of june beettle (Leucopholis irrorata chevrolat) I. Proximate and fatty acid composition - Cortez, Sharon Mendiola
ABSTRACT The proximate and fatty acid compositions of the June beetle were determined. The lot was divided into four. Each was subjected to a different treatment: raw, frozen, preprocessed, and cooked, to evaluate the changes in their nutritional content as the June beetle undergoes processing. The amount of moisture was determined using the ordinary air oven set at 100-105°C while the crude fat was determined using Soxhlet apparatus. the crude protein content was determined using the modified Kjeldahl method. Total available and unavailable carbohydrates were determined using the Clegg-Anthrone method and the classical Wendee method, respectively. Dry ashing method was utilized in determining the amount of ash. As for the fatty acid profile, Bligh and Dryer method was used to extract fatty acids. After which, quantitation and identification of each fatty acids were done with the use of a gas chromatograph. The proximate content of the June beetle changed as it went through processing. The drying effect and the uptake of cooking oil had a significant role in the change of its proximate composition. Moreover, the dilution effect of vinegar on the preprocessed lot also contributed to the change in its proximate content. The predominant fatty acids detected in the June beetle were oleic, palmitic, linoleic, and myristic acids. The predominance of lauric acid in the cooked June beetle is due to the cooking oil used in frying. Unidentified fatty acids were also detected. These are unsaturated aalogs of the saturated fatty acids to which their retention time is nearest.